Educational Neuroscience in Academic Environment. A Conceptual Review - Gkintoni, Evgenia; Halkiopoulos, Constantinos; Antonopoulou, Hera (Technium Social Sciences Journal, 2023)
Neuroscience uses cellular and molecular biology, anatomy and physiology, human behavior and cognition, and other disciplines to map the brain at a mechanistic level. Mapping all the cell-to-cell communication networks — the brain circuits that process all thoughts, emotions, and behaviors — is one of the most significant challenges of contemporary neuroscience. Neuroplasticity, the brain’s capacity to form new neural connections and circuits, is the starting point and foundation of any learning process. Neuroscience can serve as a foundation for education in the same way that biology serves as a foundation for medicine, meaning that each field retains its creativity but cannot violate the laws of the other. This work examines the relationship between neuroscience and educational practice, focusing on how teachers and school psychologists can use potential research findings from these fields to bridge the gap between them.